TP53I13 promotes metastasis in glioma via macrophages, neutrophils, and fibroblasts and is a potential prognostic biomarker - Ge, Xinqi; Xu, Manyu; Cheng, Tong; Hu, Nan; Sun, Pingping; Lu, Bing; Wang, Ziheng; Li, Jian (Frontiers in Immunology, 2022)
Background: A protein-coding gene, TP53I13 (Tumor protein p53 inducible protein 13), can play a role of suppressor of tumor impeding proliferation of tumor cell in case of overexpressed. Nevertheless, the expression pattern as well as the exact role of TP53I13 in the progression and occurrence of glioma (LGG and GBM) have yet to be deciphered. This research aims to evaluate the TP53I13’s prognostic role in glioma through analysis of comprehensive bioinformatics. Methods: With the help of multiple databases, TP53I13’s expression-level was evaluated and assessed, including GeneMANIA, GEPIA, TISIDB, The Tumor Immune Estimation Resource (TIMER), the Cancer Genome Atlas (TCGA), and Chinese Glioma Genome Atlas (CGGA). TP53I13 expression was further explored through immunohistochemistry (IHC) and multiplex immunohistochemistry (mIHC). Considering the gene set enrichment analysis (GSEA), the biological and metastatic processes connected to TP53I13 were assessed. Results: The TP53I13 expression level was mainly upregulated in tumor tissues in comparison to the normal tissues. TP53I13’s high expression level correlated with poor survival outcomes in both the TCGA and CGGA databases. Multivariate Cox analysis revealed that TP53I13 might play a role of independent prognostic reflector of glioma, and increased expression of TP53I13 was significantly correlated with PRS type, status, 1p/19q codeletion status, IDH mutation status, chemotherapy age, and grade. Through CIBERSORT analysis and TIMER, the TP53I13 expression level was correlated with macrophages, neutrophils, dendritic cells, and T cells. correlated By performing GSEA, we found that TP53I13 is closely with the p53 signaling pathway, DNA replication, and the pentose phosphate pathway. Conclusion: Our findings reveal that TP53I13 is closely associated with glioma and affects the survival outcomes of glioma patients to a large extent. Additionally, TP53I13 is an independent indicator and plays an imperative role in tumor-infiltrating immune cells. These data suggest that TP53I13 might be considered as a new biomarker for immune infiltration and glioma prognosis.